Natural triterpenic diols promote apoptosis in astrocytoma cells through ROS-mediated mitochondrial depolarization and JNK activation. - Rubén Martín; Elvira Ibeas; Juliana Carvalho-Tavares; Marita Hernández; Valentina Ruiz-Gutierrez; María Luisa Nieto (PLoS ONE)
Background Triterpene alcohols and acids are multifunctional compounds widely distributed throughout the plant kingdom that exhibit a variety of beneficial health properties, being synthetic analogs of oleanolic acid under clinical evaluation as anti-tumoral therapeutic agents. However, the antineoplastic activity of two natural occurring triterpenoid alcohols extracted from olive oil, erythrodiol (an intermediate from oleanolic acid), and its isomer, uvaol, has barely been reported, particularly on brain cancer cells. Astrocytomas are among the most common and aggressive type of primary malignant tumors in the neurological system lacking effective treatments, and in this study, we addressed the effect of these two triterpenic diols on the human 1321N1 astrocytoma cell line. Principal findings Erythrodiol and uvaol effectively affected cell proliferation, as well as cell cycle phases and induced 1321N1 cell death. Both triterpenes successfully modulated the apoptotic response, promoting nuclear condensation and fragmentation. They caused retraction and rounding of cultured cells, which lost adherence from their supports, while F-actin and vimentin filaments disappeared as an organized cytoplasmic network. At molecular level, changes in the expression of surface proteins associated with adhesion or death processes were also observed. Moreover, triterpene exposure resulted in the production of reactive oxygen species (ROS) with loss of mitochondrial transmembrane potential, and correlated with the activation of c-Jun N-terminal kinases (JNK). The presence of catalase reversed the triterpenic diols-induced mitochondrial depolarization, JNK activation, and apoptotic death, indicating the critical role of ROS in the action of these compounds. Conclusions Overall, we provide a significant insight into the anticarcinogenic action of erythrodiol and uvaol that may have a potential in prevention and treatment of brain tumors and other cancers.